Money laundering: Analysis on the placement methods - Zul Kepli, Mohd Yazid; Nasir, Maruf Adeniyi (Zes Rokman Resources, 2016)
The International Monetary Fund (IMF) in 2015 estimated the size of money laundering to be at 2-5% of the world Global Domestic Production (GDP) with around USD800 billion to USD2 trillion being laundered. The global criminal activities are on the rise and the contribution of money laundering to exacerbate the problems associated with the upsurge in the criminal activities is unquantifiable.